Macromolecules containing metal and metal-like elements (Wiley-Interscience, 2005)
This series provides a useful, applications-oriented forum for the next generation of macromolecules and materials. Applications include non-linear optical materials, specialty magnetic materials, liquid crystals, anticancer and antiviral drugs, treatment of arthritis, antibacterial drugs, antifouling materials, treatment of certain vitamin deficiencies, electrical conductors and semiconductors, piezoelectronic materials, electrodes, UV absorption applications, super-strength materials, special lubricants and gaskets, selective catalytic and multi-site catalytic agents.